"The Mayan in the Mall. Globalization, Development and the Making of Modern Guatemala", de J.T. Way. - Salas Acuña, Erick Francisco (Universidad de Costa Rica, 2013)
Reseña del libro "The Mayan in the Mall. Globalization, Development and the Making of Modern Guatemala".